O crime de corrupção eleitoral : bem jurídico, ofensividade e seus fundamentos constitucionais - Sganzerla, Samuel (2017)
The present dissertation proposes to examine the crime of electoral corruption from the perspective of crime as an offense to legal interests. In order to do so, the study turns, in the first instance, to the aspects pertinent to the concepts of legal interest and offensiveness, in order to delimit the panorama on which the examination in the specific question unfolds. Subsequently, it works on the constitutional and material foundations of political rights and electoral law in our legal system, especially regarding the rule of law, democracy, democratic principle, suffrage, popular sovereignty, citizenship, since they are essential to understand the legal interests protected by such institutes and, from then on, the nature of the crime of electoral corruption and its object of criminal protection. Finally, a more specific analysis is made of the selected crime, with the purpose of discussing its dogmatic basis and of identifying the criminal-legal interest(s) protected by the standard and the televance of the concept of offensiveness on the species.